Clinical case of COVID-19 course in a child with aplastic anemia - D. O. Ivanov; Yu. V. Petrenko; R. A. Nasyrov; V. A. Reznik; V. N. Timchenko; T. A. Kaplina; S. L. Bannova; O. L. Krasnogorskaya; M. B. Paneyakh; E. P. Fedotova; G. V. Kondratyev; M. D. Subbotina; et al. (Журнал инфектологии)
The problem of the non-smooth course of COVID-19 and deaths in children with severe comorbid pathology is urgent. Among all registered cases of a new coronavirus infection in the Russian Federation, children account for up to 8,6%, of which severe forms are noted, as a rule, in patients with concomitant diseases. A clinical observation of the course of a new coronavirus infection in a child with a severe form of idiopathic aplastic anemia complicated by pancytopenia is presented. COVID-19 infection caused a sharp deterioration in the child’s condition. Despite the use of modern methods of therapy, there was a rapid deterioration of clinical and laboratory parameters: an increase in febrility, respiratory failure, interstitial changes in the lungs, a decrease in oxygen saturation to 70%, hemorrhagic, anemic syndromes and multiple organ failure with the development of a fatal outcome. Aplastic anemia is a factor predisposing to the severe course of COVID-19 and contributing to an unfavorable outcome.